Progression of neuropathic pain after acute spinal cord injury: a meta-analysis and framework for clinical trials - Warner, Freda M.; Weidner, Norbert (Journal of neurotrauma, 2019)
The translation of therapeutic interventions to humans with spinal cord injury with the goal of promoting growth and repair in the central nervous system could, inadvertently, drive mechanisms associated with the development of neuropathic pain. A framework is needed to evaluate the probability that a therapeutic intervention for acute spinal cord injury modifies the progression of neuropathic pain. We analyzed a large, longitudinal dataset from the European Multi-Center Study about Spinal Cord Injury (EMSCI) and compared these observations with a previously published Swedish/Danish cohort. A meta-analysis was performed to produce aggregate estimates for the transition period between 1-6 months and the transition period between 1-12 months after injury. A secondary analysis used logistic regression to explore associations between the progression of neuropathic pain and demographics, pain characteristics, and injury characteristics. For overall neuropathic pain, 72% presenting with pain symptoms at one month reported persisting symptoms at six months, and 23% who did not have neuropathic pain at one month later had it develop. From 1-12 months, there was a similar likelihood of pain persisting (69%) and slightly higher rate of pain developing (36%). Characteristics that were significantly associated with the progression of pain included age and sensory and motor preservation. We provide historical benchmarks for estimating the progression of neuropathic pain during the first year after acute SCI. This information will be useful for comparison and evaluating safety during early phase acute spinal cord injury trials.
Published online:18 December 2018
Gesehen am 26.06.2019